2019
DOI: 10.1002/dta.2685
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a thermal degradation product of CUMYL‐PEGACLONE and its detection in biological samples

Abstract: The structural diversity of synthetic cannabinoids makes it a challenging task to have a comprehensive screening method for this class of drugs. The difficulty is increased by the fact that some synthetic cannabinoids undergo thermal decomposition during common routes of administration, such as smoking or vaping. CUMYL‐PEGACLONE is a relatively new synthetic cannabinoid which has a structural variant from most other synthetic cannabinoids: a γ‐carbolinone core. To investigate its thermal stability, CUMYL‐PEGAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…5F‐AB‐PINACA ( 80 ) and 5F‐AMB ( 81 ) are both examples of indazole SCRAs which bear a 5‐ fluoropentyl “tail group”. N ‐ n ‐Pentyl‐γ‐carbolinone ( 84 ) is the major thermal degradant of CUMYL‐PEGACLONE ( 63 )…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5F‐AB‐PINACA ( 80 ) and 5F‐AMB ( 81 ) are both examples of indazole SCRAs which bear a 5‐ fluoropentyl “tail group”. N ‐ n ‐Pentyl‐γ‐carbolinone ( 84 ) is the major thermal degradant of CUMYL‐PEGACLONE ( 63 )…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of the terminal fluorine atom in metabolite 83 , supports its utility as a specific metabolite marker for the consumption of 64 . Nash et al have recently investigated the thermal degradation (200–350°C) of 63 and demonstrated that the major degradant formed under such conditions is N ‐ n ‐pentyl‐γ‐carbolinone ( 84 ) . Importantly, the authors caution that the latter study may not provide an accurate thermal degradation profile of 63 , as the temperature distribution within a traditional cigarette (~ 900°C) or “e‐cigarette” (40–950°C) can vary significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,88,94 Drug thermal degradation experiments will need to consider the desired temperature range for the work; a suitable temperature range reflects the drug paraphernalia that drug users utilise which may range between: cigarettes, electronic cigarettes (E-cigs), aluminium foil, glass pipe/surface or a tube furnace. Different paraphernalia reach different temperatures; smoking for example (with a cigarette typically) can reach high temperatures up to 700-900 C and there are some toxic breakdown products that are not produced until approximately 200 C. 94,96 An 'e-cig' can have a very large temperature range; Chen et al 97 investigated the heating coil temperature for e-cigarettes under different conditions (dry, wet-through-wick and full-wet) and found that it could range from 40-950 C. Other miscellaneous paraphernalia used for heating such as a glass bulb was found to reach over 300 C when heated with a disposable lighter to heat a powder until it turned to tar. 27 Various studies have examined the temperature range for these different paraphernalia, as well as the 'optimal' temperature for an efficient combustion/heating of the product; for example, Nakahara et al 85 investigated the pyrolysis of crack and cocaine hydrochloride and their degradation products produced at different temperatures.…”
Section: Controlled Studies and The Sampling Of Drug Thermal Degradation Productsmentioning
confidence: 99%
“…Lacking in relevant structural data on these new substances, it is difficult to detect and monitor them in drug laboratories. 6 Although nuclear magnetic resonance spectroscopy shows substantial advantages in structural identification, it requires high sample purity and quantity, being difficult to effectively identify new psychoactive substances in mixtures. 7 However, with the strong separation performance and characterization of chromatography combined with mass spectrometry (MS), rich structural information on unknown substances can be obtained through multi-stage MS analysis.…”
mentioning
confidence: 99%